Self-organization and dewetting kinetics in sub-10 nm diblock copolymer line/space lithography. (23rd April 2023) - Chevalier, Xavier; Pound-Lana, Gwenaelle; Gomes Correia, Cindy; Cavalaglio, Sébastien; Cabannes-Boué, Benjamin; Restagno, Frédéric; Miquelard-Garnier, Guillaume; Roland, Sébastien; Navarro, Christophe; Fleury, Guillaume; Zelsmann, Marc
Abstract: In this work, we investigated the self-assembly of a lamellar block copolymer (BCP) under different wetting conditions. We explored the influence of the chemical composition of under-layers and top-coats on the thin film stability, self-assembly kinetics and BCP domain orientation. Three different chemistries were chosen for these surface affinity modifiers and their composition was tuned in order to provide either neutral wetting (i.e. an out-of-plane lamellar structure), or affine wetting conditions (i.e. an in-plane lamellar structure) with respect to a sub-10 nm PS- b -PDMSB lamellar system. Using such controlled wetting configurations, the competition between the dewetting of the BCP layer and the self-organization kinetics was explored. We also evaluated the spreading parameter of the BCP films with respect to the configurations of surface-energy modifiers and demonstrated that BCP layers are intrinsically unstable to dewetting in a neutral configuration. Finally, the dewetting mechanisms were evaluated with respect to the different wetting configurations and we clearly observed that the rigidity of the top-coat is a key factor to delay BCP film instability.